MicroRNAs regulate KDM5 histone demethylases in breast cancer cells. Issue 2 (1st December 2015) - Denis, Hélène; Van Grembergen, Olivier; Delatte, Benjamin; Dedeurwaerder, Sarah; Putmans, Pascale; Calonne, Emilie; Rothé, Françoise; Sotiriou, Christos; Fuks, François; Deplus, Rachel
Abstract : MicroRNAs (miRNAs) are small non-coding RNAs that post-transcriptionally regulate gene expression. Abstract : MicroRNAs (miRNAs) are small non-coding RNAs that post-transcriptionally regulate gene expression. Alteration of miRNA levels is common in tumors and contributes to the pathogenesis of human malignancies. In the present study we examined the role played by miR-137 in breast tumorigenesis. We found miR-137 levels to be lower in breast cancer cells than in their non-tumorigenic counterparts and observed reduced proliferation and migration of breast cancer cells overexpressing miR-137. We further identified KDM5B, a histone demethylase known to be involved in breast cancer tumorigenesis, as a target of miR-137. As the involvement of histone demethylases in cancer is still poorly understood and as the role of miRNAs in controlling epigenetic mechanisms in cancer is emerging, we broadened our study to the whole KDM5 histone demethylase family to see if the genes coding for these epigenetic enzymes might be regulated by miRNAs in cancer cells. We discovered that KDM5C is overexpressed in breast cancer cells, providing evidence that miR-138 regulates its expression. We found miR-138 overexpression to affect breast cancer cell proliferation. Altogether, our findings suggest that miRNAs may regulate KDM5 histone demethylase levels in breast cancer and thereby control breast cancer cell proliferation and migration.